Work engagement and associated factors among healthcare professionals in the post-pandemic era: a cross-sectional study - Wang, Yiya; Tang, Li; Li, Lezhi (Frontiers in Public Health, 2023)
Background With the shift of strategy in fighting COVID-19, the post-pandemic era is approaching. However, the “hard times” for healthcare systems worldwide are not yet ending. Healthcare professionals suffer negative impacts caused by the epidemic, which may seriously threaten their work motivation, concentration, and patient safety. Objective Investigating the status and factors associated with Chinese healthcare professionals’ work engagement in the post-pandemic era. Methods A cross-sectional study was conducted to investigate healthcare professionals from 10 hospitals in Hunan Province. Data were collected using demographic characteristics, Generalized Anxiety Disorder-2, Patient Heath Qstionaire-2, Utrecht Work Engagement Scale, Work-Related Basic Need Satisfaction Scale, National Aeronautics and Space Administration-Task Load Index, and self-compassion scale. Descriptive and multiple linear regression analyses explored the factors associated with work engagement. Results A total of 1,037 eligible healthcare professionals participated in this study, including 46.4% of physicians, 47.8% of nurses, and 5.8% of others. The total mean score of work engagement was 3.36 ± 1.14. The main predictor variables of work engagement were gender (p = 0.007), years of work experience (p < 0.001), whether currently suffering challenges in the care of patients with COVID-19 (p = 0.003), depression (p < 0.001), work-related basic need satisfaction (p < 0.001), and mindfulness (p < 0.001). Conclusion Healthcare professionals have a medium level of work engagement. Managers need to pay attention to the physical and psychological health of healthcare professionals, provide adequate support, help them overcome challenges, and acknowledge their contribution and value to improve their work engagement, enhance the quality of care and ensure patient safety.